Liberalisasi Perdagangan Jasa Penerbangan Melalui Kebijakan Open Sky dan Implikasinya Bagi Indonesia - Emmy Latifah (Jurnal Hukum IUS QUIA IUSTUM, 2011)
The research problems are: first, implementation of open sky policy in the frame of flight service trade liberalization based on Act No. 1 of 2009 on Flight; second, the implication of enactment of open sky policy for Indonesia in the frame of flight service trade.This research is empirical legal research. The data used is primary and secondary data which are analyzed using editing analysis style technique later.This is caused by many factors which are: the government’s lack of preparation in protecting domestic flight industry by not providing clear regulation in determining tariff, the operator’s lack of preparation in conducting flight service, the lack of facility in pursuing open sky. There is economical, social, defense and security implication from the application of open sky policy for Indonesia. However, the most significant implication from these impacts is economy defense, and security implication.